Rethinking Hybrid and Remote Work in Higher Education - Allen Milton, Sharlene (American Journal of STEM Education, 2024)
Rethinking Hybrid and Remote Work in Higher Education brings together scholarship from diverse regions including North America, South America, Africa, Southeast Asia, and East Asia, presenting varied perspectives on crucial issues in global higher education. The book is structured into three sections and seventeen chapters, focusing on opportunities and challenges, perceptions, policies, practices, and case studies related to hybrid and remote work in academia. This review will examine the prologue, sections one through three, and the conclusion.